Assessment of vacuum-dried peppermint (Mentha piperita L.) as a source of natural antioxidants. (1st January 2016) - Uribe, Elsa; Marín, Daniela; Vega-Gálvez, Antonio; Quispe-Fuentes, Issis; Rodríguez, Angela
Highlights: Peppermint can play an important role as a source of bioactive compounds. Vacuum drying preserves some quality parameters of dried peppermint. The vacuum-dried peppermint can be a potential ingredient of functional foods. Abstract: The purpose of this study was to investigate the effect of temperature in the vacuum drying process of Mentha piperita L. (50 to 90 °C). Generally, drying processes affect the quality of product, however, vacuum drying works under sub-atmospheric pressures. In order to investigate how temperature affects this herb, as to color, chlorophyll, total phenolic (TPC), total flavonoid (TFC) contents, antioxidant activity by DPPH and ORAC methods. Mineral, vitamin C and sugar contents were also evaluated. A slight change in color and chlorophyll content was observed in the samples. The highest values for TPC, TFC and antioxidant activity methods were obtained at 50 and 70 °C however, a decrease in the vitamin C content was observed. Minerals such as K, Ca, Mg and Na were found. Sucrose showed the highest sugar content. This work suggests that M. piperita L. can be used as a natural antioxidant, whether fresh or dried.